2012
DOI: 10.1111/j.2044-8287.2012.02078.x
|View full text |Cite
|
Sign up to set email alerts
|

Trajectories of BMI from early childhood through early adolescence: SES and psychosocial predictors

Abstract: What is already known? Past research has found evidence that patterns of childhood overweight are impacted by socioeconomic status through psychosocial factors like parenting and depression. This evidence is often limited to individual points in time where neglectful, permissive, and authoritarian parenting and higher levels of maternal depression are associated with higher levels of overweight status among children from infancy to adolescence. However, little research has linked together whether the children … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
58
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(61 citation statements)
references
References 41 publications
3
58
0
Order By: Relevance
“…Both positive (Ertel et al, 2012; Ertel et al, 2010) and null (Ajslev et al, 2010; Ertel et al, 2012; Ertel et al, 2010; Grote et al, 2010; Lane et al, 2013; Wang et al, 2013) associations were observed between maternal depression in the first 6 months of life and child weight outcomes. In a US sample, Ertel et al (2010) observed that children exposed to maternal depression had greater overall adiposity (sum of subscapular skinfold and triceps skinfold thickness) of 1.14mm, but not BMI z-score, central adiposity, or risk for overweight, compared to those not exposed to maternal depression.…”
Section: Resultsmentioning
confidence: 96%
See 4 more Smart Citations
“…Both positive (Ertel et al, 2012; Ertel et al, 2010) and null (Ajslev et al, 2010; Ertel et al, 2012; Ertel et al, 2010; Grote et al, 2010; Lane et al, 2013; Wang et al, 2013) associations were observed between maternal depression in the first 6 months of life and child weight outcomes. In a US sample, Ertel et al (2010) observed that children exposed to maternal depression had greater overall adiposity (sum of subscapular skinfold and triceps skinfold thickness) of 1.14mm, but not BMI z-score, central adiposity, or risk for overweight, compared to those not exposed to maternal depression.…”
Section: Resultsmentioning
confidence: 96%
“…While this positive association was observed in complete-case analysis, this effect was not observed when multiple-imputation methods were employed. The remaining studies failed to find an association between postpartum maternal depression and child weight outcomes, including child overweight (Ajslev et al, 2010; Wang et al, 2013), obesity (Ajslev et al, 2010), growth in child BMI percentile (Lane et al, 2013), or weight-for-length, triceps skinfold thickness, and subscapular skinfold thickness z-score (Grote et al, 2010). …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations